SISTEM PAKAR MENDIAGNOSA PENYAKIT PERUT DENGAN METODE FORWARD CHAINING - Christy Natalia Gultom; jenie sundari; Nila Hardi (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2023)
— At present there are still many people who do not know about the types of stomach diseases that exits. In general, people only understand 1 or 2 types of stomach disease that exist and underestimate the syptoms of stomach pain they experience. While an upset stomach if not immediately known and treated can be a very dangereous disease that can cause death for sufferers anyway. Therefore, it is very important for the public to know the beginning and existing stomach aliments. Therefore, the authors provide a solution by creating an Expert Systems to Diagnose Stomach Diseases that can help the community in diagnosing stomach ailments that they are experiencing. Experts system is a computer application that is intended to assist in making decisions or solving problems in a spesific field. All the knowledge needed in the expert system is an amalgamation of several experts made by doctors, all the accuarcy data can be trusted. This research used the forward chaining method to get conclusion from the syptoms of stomach disease experienced by the community. Keywords: disease, stomach,expert, forward, chaining